2019
DOI: 10.1111/itor.12649
|View full text |Cite
|
Sign up to set email alerts
|

Empirical surveys of frontier applications: a meta‐review

Abstract: This contribution is the first attempt to systematically review all empirical surveys that so far have been made available in the broad field of efficiency and productivity analysis using frontier estimation methodologies. We provide a systematic bibliometric review on the many empirical surveys in the field of efficiency and productivity analysis, the most relevant concepts, areas, overlaps, and potentials to explore from its introduction to the most recent surveys. We combine the United Nations’ Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 173 publications
0
34
0
4
Order By: Relevance
“…Charnes et al [ 37 ] and Banker et al [ 38 ] through a mathematical linear dual formulation for multiple outputs/inputs configurations in the efficiency problem introduced the so-called data envelopment analysis (DEA). Today, this is the most common approach to assess the efficiency and productivity of many decision-making units (DMUs) in the number of surveys, applications, methodologies, and computational developments [ 39 , 40 ]. The mathematical programming provides, among other results, the optimal amount of resources to save or products to increase so that an inefficient service unit becomes efficient.…”
Section: Methodsmentioning
confidence: 99%
“…Charnes et al [ 37 ] and Banker et al [ 38 ] through a mathematical linear dual formulation for multiple outputs/inputs configurations in the efficiency problem introduced the so-called data envelopment analysis (DEA). Today, this is the most common approach to assess the efficiency and productivity of many decision-making units (DMUs) in the number of surveys, applications, methodologies, and computational developments [ 39 , 40 ]. The mathematical programming provides, among other results, the optimal amount of resources to save or products to increase so that an inefficient service unit becomes efficient.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding scope of efficiency and productivity studies, Daraio et al (2020) recently showed that review studies on frontier applications cover 13 out of the 22 areas of economic activity as described by the ISIC scheme. They also showed that, the review studies represented categories A to I of the JEL classification scheme.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Ranking Decision Making Units (DMUs) according to their productive performance has been the objective of Data Envelopment Analysis (DEA) applications in many sectors of economic activities for classifying both efficient and inefficient units [1,2,3]. Ranking service units provide valuable discriminations that support strategic decision-making by creating incentive structures for rewarding efficient managers, teams, resource allocations, recognizing prospective policies and best practices, changing misleading business competencies, operations and activities, and developing sustainable directions for continuous improvement [4].…”
Section: Introductionmentioning
confidence: 99%